Analysis of renewable energy subsidy in China under uncertainty: Feed-in tariff vs. renewable portfolio standard. (March 2021) - Yang, Dong-xiao; Jing, Ya-qiang; Wang, Chan; Nie, Pu-yan; Sun, Peng
Abstract: Environmental pollution, climate warming and other issues have become global issues, and the use of renewable energy as the best way to solve the problem has gradually attracted the attention of all countries. Uncertainty has an important effect on the production of renewable energy. Through a two-stage model, this paper compares the effects of feed-in tariff (FIT) and renewable portfolio standard (RPS) in the developing renewable energy industry under uncertainty. The results show that the FIT have higher expected output and profit, and lower market prices. The risks of production and gain is of relatively more significant. By contrast, the production and profit of RPS remain relatively more stable. When the cost of renewable energy is high, the incentive effect of the policy under FIT is better. As the cost decreases, the incentive effect under RPS will continually increase. In summary, at low cost, the output of renewable energy is proportional to the intensity of the policy under the two policies. We can further conclude that FIT is suitable for the early stage of the development of the renewable energy industry. Once the industry is mature, we can strategically integrate FIT and RPS to ensure a healthy and sustainable development.